2014
DOI: 10.1016/j.shaw.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Experiences of Risks among Pupils in Vocational Education

Abstract: BackgroundYoung male and female workers are over-represented in statistics concerning negative outcomes of poor work environment and risky work. Young workers often have low awareness of risk, a lack of safety training, and inadequate introduction to the work. The aim of this study was to identify the knowledge and experiences of pupils of vocational schools concerning potential work environment risks in their future work.MethodsThe study design was a dual one, and included a questionnaire and focus group inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 16 publications
2
14
0
Order By: Relevance
“…Results also suggest participants report a higher frequency of adoption of behaviours related to the concern for physical and social environment in comparison with behaviours related to compliance with rules and procedures and with participation and initiatives related to prevention. These results are consistent with a prior study that found that vocational students consider prevention mostly as personal concrete actions related to working equipment (Andersson et al 2014) and with another study suggesting that social relations have an important effect on behaviours and attitudes toward prevention among young workers (Breslin et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Results also suggest participants report a higher frequency of adoption of behaviours related to the concern for physical and social environment in comparison with behaviours related to compliance with rules and procedures and with participation and initiatives related to prevention. These results are consistent with a prior study that found that vocational students consider prevention mostly as personal concrete actions related to working equipment (Andersson et al 2014) and with another study suggesting that social relations have an important effect on behaviours and attitudes toward prevention among young workers (Breslin et al 2007).…”
Section: Discussionsupporting
confidence: 92%
“…In the 2013 study, 'Knowledge and experiences of risks among pupils in vocational education', Andersson et al (2014), the researchers visited the schools, informed the pupils about the study, and asked them to complete a questionnaire with questions about their opinions of attractive work (baseline). Absent pupils received a letter with information about the study; in these cases, the teacher administrated the distribution of the questionnaire and sent the completed questionnaire back to the researchers by post.…”
Section: Methodsmentioning
confidence: 99%
“…Another problem is that workers often do not want to use Personal Protective Equipment (PPE) that has been provided for various reasons. Also, there are workers who are less understanding about OHS [1]. Most supervisors did not receive information from the schools as to what should be included when introducing OHS at workplace [2].…”
Section: Introductionmentioning
confidence: 99%
“…The questions in this study based on CIPP model background and concept evaluation (Context, Input, Process, Product) described as: (1) The following describes the instrument used in this study.…”
Section: Introductionmentioning
confidence: 99%